2019
DOI: 10.3390/ijms20030695
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Circulating Fibroblast Growth Factor 23 (FGF23) and Prognosis in Cancer Patients with Bone Metastases

Abstract: The fibroblast growth factor (FGF) signaling pathway plays a key role in tumorigenesis and is recognized as a potential therapeutic target. In this study, the authors aimed to assess the impact of serum FGF23 levels in the prognosis of patients with cancer and bone metastases from solid tumors. A cohort of 112 patients with cancer and metastatic bone disease were treated with bone-targeted agents (BTA). Serum baseline FGF23 was quantified by ELISA and dichotomized in FGF23high and FGF23low groups. Additionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Genomic aberrations in the FGF19 subfamily members have rarely been associated with a role in cancer progression, with the exception of an SNP in FGF23 that has been linked to increased risk of prostate cancer [ 169 ]. Although not directly linked to the SNP, FGF23 overexpression has also been associated with reduced overall survival and shortened time to occurrence of bone metastases [ 170 ] A large proportion of endometrial cancers are associated with metabolic disorders, including obesity. FGF21 and FGF23 expression have been implicated in endometrial cancer due to their association with increased expression of leptin (LEP), a hormone produced in adipose tissue.…”
Section: Fgf Signaling Diversity In Cancermentioning
confidence: 99%
“…Genomic aberrations in the FGF19 subfamily members have rarely been associated with a role in cancer progression, with the exception of an SNP in FGF23 that has been linked to increased risk of prostate cancer [ 169 ]. Although not directly linked to the SNP, FGF23 overexpression has also been associated with reduced overall survival and shortened time to occurrence of bone metastases [ 170 ] A large proportion of endometrial cancers are associated with metabolic disorders, including obesity. FGF21 and FGF23 expression have been implicated in endometrial cancer due to their association with increased expression of leptin (LEP), a hormone produced in adipose tissue.…”
Section: Fgf Signaling Diversity In Cancermentioning
confidence: 99%
“…Because bone is the main site of FGF23 production, malignancies typically affecting or arising from bone may have a link to FGF23. In patients with bone metastasis due to different solid tumors, a higher FGF23 plasma concentration is associated with shorter survival and shorter time to skeletal-related events ( Mansinho et al, 2019 ). Patients with myelodysplastic syndrome (MDS) characterized by impaired hematopoiesis in the bone marrow have a higher FGF23 plasma concentration that is associated with anemia and lower bone mineralization ( Weidner et al, 2020 ).…”
Section: Fgf23 and Cancermentioning
confidence: 99%
“…Choudhary et al reported for the first time that the presence of prostate cancer cells significantly stimulates the expression of FGF23 by osteocytes [ 82 ]. Interestingly, other researchers suggested that FGF23 may play a role in cancer [ 84 , 85 , 86 ]. For example, FGF23 may act as an autocrine, paracrine and/or endocrine growth factor in prostate cancer progression, but the relative importance of each factor depends on tumor expression level, tumor site, and underlying disease state [ 85 ].…”
Section: Osteocytes: Their Physiology and Possible Contributions Tmentioning
confidence: 99%
“…Mansinho et al assigned a negative prognostic meaning to FGF: low baseline serum FGF23 levels correlated with longer overall survival and onset of SREs in metastasis-bearing patients [ 84 ].…”
Section: Osteocytes: Their Physiology and Possible Contributions Tmentioning
confidence: 99%